2016
DOI: 10.21475/poj.16.09.03.p7724
|View full text |Cite
|
Sign up to set email alerts
|

The role of sucrose metabolizing proteins in hyperosmotic stress tolerance in sweet sorghum (Sorghum bicolor L. Moench)

Abstract: Sugar accumulation is a common metabolic response under drought stress conditions. However, studies on the underlying molecular mechanisms of sugar accumulation under stress remain restricted. This study explores the role of sucrose metabolizing proteins in conferring tolerance to drought-induced hyperosmotic stress, and ultimately osmotic adjustment in sorghum. The effect of stress on sugar content, enzyme activity and gene expression was investigated. Sweet sorghum varieties (ICSV213 and ICSB338) differing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…The highest concentrations of glucose and fructose were recorded in the accession G10. Similar trend of variations for sucrose and hexoses was observed for two sorghum varieties (ICSV213, ICSB338) subjected to a post-anthesis drought through a pot experiment (Njokweni et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…The highest concentrations of glucose and fructose were recorded in the accession G10. Similar trend of variations for sucrose and hexoses was observed for two sorghum varieties (ICSV213, ICSB338) subjected to a post-anthesis drought through a pot experiment (Njokweni et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, five SPS genes were regulated by uniconazole under drought stress (Supplementary Table S5 ). Previous studies have shown that sucrose synthase genes are regulated by drought stress, improving hyperosmotic stress tolerance of plants in relation to the accumulation of starch and sucrose metabolism proteins 46 . The present study described that two SuSy genes were differentially expressed in drought stress induced by uniconazole (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of sugar in sorghum varieties is related to defensive mechanisms in stress situations, which guarantees the metabolic activities of plant and grain development. 75 In the present study, phenolic acids predominant in sorghum grains were detected, including three cinnamic acids, caffeic acid (m/z 179), ρ-coumaric acid (m/z 165) and ferulic acid (m/z 193), in addition to the chlorogenic acid, caffeoylquinic acid (m/z 353), and its 3,5-di-O-caffeoylquinicacidmethylester derivative (m/z 535), and a benzoic acid, protocatechic acid (m/z 153). 76 Cinnamic acids are found whole or combined with other molecules such as glucose, esters and other acids, the most common being chlorogenic acid, a combination of quinic and caffeic acid.…”
Section: (−)Ps-ms Fingerprintsmentioning
confidence: 99%